Instruments for analysing the influence of advertising on children's food choices - Gwozdz, W; Reisch, L.A (International Journal of Obesity, 2011)
Objective: The aim of this report was to present methodological aspects of assessing the effects of advertising on children's food choices and preferences. Methods: Two instruments have been used: first, a choice experiment on children's food knowledge and preferences, and second, a questionnaire on children's knowledge about and attitudes towards advertising. The choice experiment employed 10 matched pairs of food items, each represented in two magazines, one that tested knowledge and the other food preferences. The children's questionnaire contained four dimensions that tested children's credibility and suspiciousness of, as well as entertainment by, advertising. Although based on already developed tools, both instruments were modified to suit the young target group and ensure cross-cultural comparability. The questionnaire was validated via Cronbach's alpha and factor analysis. Subjects: A total of 393 children aged 5–11 years from seven European countries participated in the study. Results: Both instruments proved to be valid and reliable to analyse the food knowledge and preferences of children, as well as knowledge about and attitudes towards advertising. While 92.2% of the children predominantly recognised the healthier food, only 33.2% also preferred the healthier food. The Cronbach's alpha values for the dimensions were 0.470 for credibility, 0.409 for suspiciousness and 0.295 for entertainment factor. The gathered data revealed that children are rather critical and suspicious of advertising and only moderately entertained. Conclusion: Both instruments are applicable for the 5- to 11-year-old age group in different European countries. Descriptive results indicate additional insights into the effects of advertising on children's food knowledge, preferences and food choice.